Identification of heterologous Torque Teno Viruses in humans and swine - Ssemadaali, Marvin A. (Sci Rep, 2016)
Torque Teno Viruses (TTVs) are ubiquitous viruses which are highly prevalent in several mammalian species. Human TTV’s are epidemiologically associated with several human disease conditions such as respiratory illnesses, auto-immune disorders and hepatitis. Recently it was found that swine TTV’s (TTSuVs) can act as primary pathogens. The common occurrence of TTVs as environmental contaminants and the increasing interest in the use of swine organs for xenotransplantation lend importance to the question of whether TTV’s can cross-infect across species. In this study, we examined human and swine sera by swine or human TTV-specific PCRs, to determine whether swine TTVs (TTSuV) DNA can be detected in humans and vice versa. Surprisingly, both human and TTSuV DNA were present in a majority of the samples tested. Transfection of human PBMC’s with TTSuV1 genomic DNA resulted in productive viral infection which was sustained for the three serial passages tested. Lymphoproliferative responses in infected human PBMCs were diminished when compared to the controls. Furthermore, mild to moderate antibody responses against the TTSuV1 ORF2 protein was detected in 16 of the 40 human sera by ELISA. Therefore, these study findings provide initial and fundamental evidence for possible cross-species transmission of TTVs.